Artificial Intelligence and Education: A Study on Secondary-Level Community Schools of Waling Municipality, Nepal - Dumre, Resham (An ENDEAVOUR: Journal of Academia and Research, 2026)
The rapid advancement of artificial intelligence (AI) has transformed educational practices worldwide, particularly in teaching and learning processes. This study investigates the integration of AI in pedagogical practices in secondary-level community schools in Waling Municipality, Nepal. In this study, sequential mixedmethod research design was employed to explore a comprehensive understanding of AI use in classroom practices. Quantitative data were collected through a structured questionnaire administered to 115 teachers, while qualitative data were gathered through classroom observations of three teachers. Quantitative data were analyzed using descriptive statistics, including frequencies and percentages, whereas qualitative data were analyzed using thematic analysis. Teachers reported that AI significantly supports lesson planning, enhances student engagement, reduces workload, and improves instructional strategies. Qualitative observations further indicate that AI integration fosters motivation, creativity, collaboration, and student-centered learning when blended with traditional teaching approaches. However, several challenges persist, including insufficient training, limited digital infrastructure, ethical concerns, plagiarism, and potential dependence on AI tools. The study concludes that AI holds strong potential to transform pedagogical practices in community schools if supported by systematic teacher training, reliable infrastructure, and ethical policy frameworks. The findings have important implications for teachers, school administrators, policymakers, and future research in AI-driven education in resource-constrained contexts.